Structure‐Guided Discovery of a Potent and Selective Cell‐Active Inhibitor of SETDB1 Tudor Domain. Issue 16 (8th March 2021) - Guo, Yinping; Mao, Xin; Xiong, Liang; Xia, Anjie; You, Jing; Lin, Guifeng; Wu, Chengyong; Huang, Luyi; Wang, Yiwei; Yang, Shengyong
Abstract: SET domain bifurcated protein 1 (SETDB1) is a histone lysine methyltransferase that promotes the silencing of some tumour suppressor genes and is overexpressed in many cancers. SETDB1 contains a unique tandem tudor domain (TTD) that recognizes histone H3 sequences containing both methylated and acetylated lysines. Beginning with the identification of a hit compound (Cpd1 ), we discovered the first potent and selective small molecule SETDB1‐TTD inhibitor ( R, R )‐59 through stepwise structure‐guided optimization. ( R, R )‐59 showed a KD value of 0.088±0.045 μM in the ITC assay. The high potency of ( R, R )‐59 was well explained by the cocrystal structure of the ( R, R )‐59 ‐TTD complex. ( R, R )‐59 is an endogenous binder competitive inhibitor. Evidence has also demonstrated its cellular target engagement. Interestingly, the enantiomer ( S, S )‐59 did not show activity in all the assays, highlighting the potential of ( R, R )‐59 as a tool compound in exploring the biological functions of SETDB1‐TTD. Abstract : The first potent and selective small‐molecule SETDB1 tandem tudor domain (TTD) inhibitor, ( R, R )‐59, is reported. ( R, R )‐59 is an endogenous binder‐competitive inhibitor and also showed activities in intact cells. The enantiomer ( S, S )‐59 did not show any activity.